Environmental-impact assessments at airport level of Clean Sky 2 technologies - Eenige, M.J.A. van; Ommeren, T.E. van (IOPscience, 2023)
GREENPORT2050 is a project within Clean Sky 2 Technology Evaluator. Its objective is to assess the environmental impact up to 2050 at airport level of technologies developed in the Clean Sky 2 Programme for fixed-wing aircraft. With these assessments, it complements the environmental-impact assessments of those technologies at the other two levels in Clean Sky 2 Technology Evaluator: aircraft and air-transport system level. This paper provides an overview of the systematic approach for airport-level assessments in GREENPORT2050 and of the indicators to quantify impacts in these assessments.